Permanence and Periodic Solution of Predator-Prey System with Holling Type Functional Response and Impulses - Weibing Wang; Jianhua Shen; Juan J. Nieto (Discrete Dynamics in Nature and Society)
We considered a nonautonomous two dimensional predator-prey system with impulsive effect. Conditions for the permanence of the system and for the existence of a unique stable periodic solution are obtained.